The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.12691/ajwr-2-5-4
|View full text |Cite
|
Sign up to set email alerts
|

The Physicochemical Quality of Groundwater in Relation to Surface Water Pollution in Majidun Area of Ikorodu, Lagos State, Nigeria

Abstract: The piece of investigation was carried out to study the ground water as well as surface water quality, nutrient status and physico-chemical characteristic of Majidun-Ilaje Area of Ikorodu, Nigeria. The study area is situated between 3°27 ' E-3°28 ' E longitude and 6°37 ' E latitude and covers about 1.71km 2 area of land. The present work has been conducted by monitoring two types of groundwater i.e. hand dug well water and borehole water of the community as well as the surface water i.e. river of the community… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 5 publications
1
18
1
Order By: Relevance
“…The temperature of the environmental waters and wastewaters used in this study were within the optimum temperature range for the survival of most mesophiles but the temperature recorded for borehole water is higher than the permissible standard of 25 o C (14). Generally, the temperature range of the waters recorded in this study is higher than previous studies where temperature ranges within 25±2˚C were reported (17,18,19). The variation in the temperatures may be due to seasonal and geographical influence on the samples collected.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…The temperature of the environmental waters and wastewaters used in this study were within the optimum temperature range for the survival of most mesophiles but the temperature recorded for borehole water is higher than the permissible standard of 25 o C (14). Generally, the temperature range of the waters recorded in this study is higher than previous studies where temperature ranges within 25±2˚C were reported (17,18,19). The variation in the temperatures may be due to seasonal and geographical influence on the samples collected.…”
Section: Discussioncontrasting
confidence: 51%
“…The pH values of the water and wastewater samples varied from slightly acidic to slightly alkaline (5.0-9.7) which are however slightly higher than the recommended range for wastewaters (6.5-9.0) and surface/ground waters (6.0-8.0). The acidic pH and high turbidity observed in the domestic wastewater could be influenced by the nature of the organic and inorganic contents such as sewage, detergents and toxic elements (19). Fish wastes and fish feeds contain carbonate salts that can make water more basic, hence the fairly higher alkalinity observed in fishery wastewater compared to the environmental waters.…”
Section: Discussionmentioning
confidence: 99%
“…However, for the high electrical conductivity recorded in the groundwater bodies, there are several factors which need to be taken into considerations such as the land uses and geology around the monitoring wells. Electrical conductivity was high during dry season in a majority of the monitoring wells, similar to Awoyemi et al (2014) in Lagos State, Nigeria. However, this finding contradicted the results of Reddy et al (2011) where the increasing electrical conductivity was proportionate to the increasing water table whereas this study revealed that the electrical conductivity was high in low water table during the dry season.…”
Section: Results and Discussion Groundwater Hydro Geochemistry Analysmentioning
confidence: 58%
“…That is, dissolved oxygen increases with increase in water quality and vice-versa. Bulley and Husdon [18] reported that most systems that are designed for the aerobic treatment of municipal waste recommend the dissolved oxygen concentration be maintained in the range of 0.5 -2 mg L -1 this was supported by Awoyemi et al [19]that reported a DO of 0.6 mg L -1 of a domestic wastewater. The level of DO in wastewater depicts the degree of contamination of the wastewater by organic matter.…”
Section: Resultsmentioning
confidence: 95%